Measuring information system performance in public sector: A case study of Pahang State education department / Mohd Aidil Riduan Awang Kader and Roslina Ali - Awang Kader, Mohd Aidil Riduan; Ali, Roslina (2012)
This paper aims to measure the is performance and its importance to the users particularly in public sector. Respondents comprise of a local public sector end users (employees) who had access to its Information Technology (IT) facilities and services (email, internet browsing and a host of office automation system) in Malaysia. A total of 151 responses were obtained. The specific objective of this study includes to identify the IS attribute (amongst systems quality, information quality and service quality) which is perceived to be the most significant relationship in determining end-user satisfaction. Furthermore this study seek to examine the relationship between the demographic factors of the end-users and their evaluation of the overall is performance. The findings discovered that system quality is the most significant relationship in determining end user satisfaction. However, the study has found that there is no significant relationship between the end user demographic factors and their evaluation of the overall is performance. Finding from this study could give public managers the basis to perform a benchmark amongst the different IS applications. In addition, the results of this study can at least be considered by top level management in developing the future policies and strategies to exploit its information resources, to develop its information infrastructure, and to promote the utilization of IS for the purpose of achieving more effective growth of public services.